PERAN GURU DALAM MENINGKATKAN KEMAMPUAN LITERASI SISWA PADA MATERI PAI DI KELAS V SDN 4 BANDA SAKTI KOTA LHOKSEUMAWE - Damayanti; Nurhayati (Journal of Contemporary Indonesian Islam, 2024)
The Teacher's Role in Improving Students' Literacy Ability in PAI Material in Class V SDN 4 Banda Sakti, Lhokseumawe City. Literacy covers various fields, including Islamic Religious Education lessons. However, some educators, especially PAI teachers, think that literacy is not too important to apply to students. The teaching method implemented is still monotonous. Most teachers use the lecture method, asking students to memorize, and copy notes from the blackboard. This is the problem, so that the quality of students in PAI literacy is very minimal. The focus of this research is What is the teacher's role in improving students' literacy skills in material in Class V SDN 04 Banda Sakti, Lhokseumawe City?  The method used is qualitative with data collection techniques in the form of observation, interviews, and documentation. Data analysis techniques were carried out by data reduction, data presentation, and drawing conclusionsThe results of this (1) the teacher as an educator is able to implement exemplary values for students through storytelling literacy and understanding of the contents of the Koran. (2) teacher, namely teaching how to write according to language rules, making stories, concluding, and describing (3) mentor, teacher helping students by giving additional study time, practicing writing, speech, and poetry reading skills. (4) motivators, teachers provide encouragement in the form of advice, tell stories about inspirational Islamic figures, give rewards, and add value to active students. (5) learning resources, the teacher provides knowledge to students in the form of theory, showing videos, posters, and internet-based learning